Measuring transport efficiency with adjustment of accidents: case of Taipei bus transit - Lin, Erwin T. J.; Lan, Lawrence W.; Chiu, Agnes K. Y. (My University, 2010)
While producing the desirable outputs (transport services), a bus transit occasionally also produces accidents, which may lead to fatalities, serious injuries, slight injuries and/or property losses. As such, without explicitly taking into account the negative effects of accidents on the outputs when measuring efficiency for bus transit, the interpretation of results could be misleading. To be more rational, this article proposes a stochastic production frontier model that incorporates the effects of accidents into the measurement. A case study with 10 Taipei bus transit carriers over 2001-2006 is carried out. The results show that the ranking of technical efficiency with consideration of accidents has significantly differed from that without accounting for accidents. The managerial implications suggest that bus carriers can level up their productive efficiency not only by means of decreasing the inputs and/or increasing the desirable outputs, but also by way of ameliorating their safety records.
Keywords: accidents; bus transit efficiency; stochastic frontier analysis